2009
DOI: 10.1007/s12237-009-9181-9
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Chlorophyll a Variability in the Shallow Microtidal Patos Lagoon Estuary, Southern Brazil

Abstract: In the shallow microtidal Patos Lagoon estuary, southern Brazil (32°07′ S-52°06′

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 43 publications
(51 reference statements)
4
55
0
5
Order By: Relevance
“…However, during periods of high river discharge (April, May and December 2010 and January 2011) a decrease in the phytoplankton biomass resulting in significant differences in concentrations of chlorophyll-a as between the dry and rainy seasons was observed. Very high levels of rainfall can depress the accumulation of phytoplankton biomass since they reduce the water residence time, washing out most of the organic matter produced and impeding the accumulation of phytoplankton, as observed in other estuaries (ABREU et al, 2010;ZINGONE et al, 2010). The tidal renewal of water and strong fresh water inflow due to precipitation can also promote a dilution of nutrient concentrations in the estuary, but the effects of these processes are prevented in the analysis by the use of the normalized mixing diagram.…”
Section: Discussionmentioning
confidence: 99%
“…However, during periods of high river discharge (April, May and December 2010 and January 2011) a decrease in the phytoplankton biomass resulting in significant differences in concentrations of chlorophyll-a as between the dry and rainy seasons was observed. Very high levels of rainfall can depress the accumulation of phytoplankton biomass since they reduce the water residence time, washing out most of the organic matter produced and impeding the accumulation of phytoplankton, as observed in other estuaries (ABREU et al, 2010;ZINGONE et al, 2010). The tidal renewal of water and strong fresh water inflow due to precipitation can also promote a dilution of nutrient concentrations in the estuary, but the effects of these processes are prevented in the analysis by the use of the normalized mixing diagram.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term fluctuations also result from individual species succession causing stochastic bloom occurrence: coccolithophores, dinoflagellates, cyanobacteria or diatoms can produce massive blooms under favourable growing conditions (Smayda 1998;Siegel et al 2007;Paerl et al 2010). Wind events that influence exchange of water masses with the ocean can also cause random, short-lived blooms in estuaries and coastal lagoons (Abreu et al 2010). -Shift in periodicity.…”
Section: Annual Cycles Of Phytoplankton Biomassmentioning
confidence: 99%
“…The wide variety of subtropical coastal lagoons have been classified according to the type of entrance channel into choked, restricted or leaky lagoons (Perillo et al, 1999), distinguished by the freshwater or marine prevailing influence (Abreu et al, 2010) or by the depth and substratum characteristics (Nichols and Boon, 1994). All the same, biological productivity in subtropical coastal lagoons is influenced by hydrodynamic processes such as water residence time (Badylak Cervantes-Duarte, R., Prego, R., López-López, S., Aguirre-Bahena, F., and Ospina-Alvarez, N. (2013) Annual patterns of nutrients and chlorophyll in a subtropical coastal lagoon under the upwelling influence (SW of Baja-California Peninsula), Estuarine, Coastal and Shelf Science 120, 54-63 .…”
Section: -Introductionmentioning
confidence: 99%
“…So, in the subtropical lagoons with estuarine zones the nutrient inputs are mainly connected with the rainfall season (Eyre 2000; Lehrter 2008;Abreu et al, 2010) and chlorophyll concentration increased up to four times the observed during the dry season (Phlips et al, 2012). On a local level in Bahia-Magdalena, the presence of a mangle forest in the littoral zone (Acosta Velázquez and Ruiz-Luna, 2007) and the phosphorite ores from neighboring areas that are loaded at San-Carlos port increased the ammonium and phosphate concentrations in the shore waters.Consequently, in keeping with the typology of Abreu et al (2010), Bahia-Magdalena can be classified among the coastal lagoons which have a prevailing marine influence, such as was emphasized by the salinities higher than 35 in the inner lagoon zone, showing the very scarce continental freshwater inputs during all the year (Fig.4). It is in the outer zone of the lagoon where the influence of the sea can be clearly identified.…”
mentioning
confidence: 99%